CFD Simulation Of Hydrodynamics In Counter-Current Spray Dryer Tower - Siti Ferdaus, Aspari; Law, Woon Phui; Jolius, Gimbun (Asia Pacific Publishing, 2015)
This paper presents a computational fluid dynamics (CFD) modelling of hydrodynamics in a counter-current spray drying tower. The simulations were performed using three different turbulent models, i.e. standard k-ε (SKE), Reynolds Stress Models (RSM) and the Detached Eddy Simulation (DES). The predicted airflow patterns inside the spray drying chamber were found to be in good agreement with the experimental data adapted from literature for all turbulence models tested in this work. A great potential of the DES for predicting the flow pattern in a counter-current spray dryer was uncovered as it provides more accurate predictions (around 10% deviation) compared to other models tested in this work.